2013
DOI: 10.1089/vbz.2012.1075
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofBorrelia burgdorferisensu lato inIxodes ricinusPopulations Across Central Britain

Abstract: Lyme borreliosis is rapidly emerging in the United Kingdom, with over 1000 cases per annum now reported. Lyme borreliosis is caused by the Borrelia burgdorferi sensu lato (s.l.) group of spirochetes, which are transmitted by ixodid ticks. In the United Kingdom, Ixodes ricinus is recognized as the principal vector of the spirochetes, and this tick species is widely distributed across the country. However, as yet, it is unclear whether the distribution of B. burgdorferi essentially mirrors that of its vector, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 40 publications
4
32
4
Order By: Relevance
“…Although low numbers of infected ticks were sequenced (but within the expected levels for the molecular method used), this finding is in contrast to a previous study in northern England where B. valaisiana (58%) and B. garinii (33%) were reported as the most commonly detected genotypes [33] and also to a study in Scotland which reported B. afzelii (48%) and B. garinii (36%) as the most common [35]. B. burgdorferi s.l.-infected ticks were found in all survey sites except Richmond Park; however, infected ticks have been reported here previously [36].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Although low numbers of infected ticks were sequenced (but within the expected levels for the molecular method used), this finding is in contrast to a previous study in northern England where B. valaisiana (58%) and B. garinii (33%) were reported as the most commonly detected genotypes [33] and also to a study in Scotland which reported B. afzelii (48%) and B. garinii (36%) as the most common [35]. B. burgdorferi s.l.-infected ticks were found in all survey sites except Richmond Park; however, infected ticks have been reported here previously [36].…”
Section: Discussioncontrasting
confidence: 95%
“…Forty ticks tested positive for B. burgdorferi s.l. (4·2%, 95% CI 3·01-5·7), which is similar to overall prevalence rates found in other studies in the UK [33][34][35] which reported 3·3%, 5-7·7% and 5·6%, respectively. However, direct comparisons between prevalence rates need to be made with caution due to differences in sample sizes, stages of ticks tested and molecular methods used.…”
Section: Discussionsupporting
confidence: 89%
“…were found at lower prevalences. Consistent with previous reports [9, 36], B. valaisiana was detected only in seminatural mixed woodland and B. burgdorferi ( s.s .) was detected only in coniferous woodland.…”
Section: Discussionsupporting
confidence: 93%
“…in the UK have indicated broad scale patterns in genospecies distribution. Bird-associated genospecies B. garinii and B. valaisiana appear to dominate in England [6, 35, 36], with some reports of rodent associated B. afzelii [37, 38]. In Scotland, B. afzelii appears to be the most common genospecies [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation